KONTRIBUSI LEMBAGA SENI BUDAYA ISLAM (LSBI) DALAM MERAWAT TRADISI ISLAM NUSANTARA DI KECAMATAN KASIMBAR - Mokh Ulil Hidayat (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
This research is related to the theme of the Islamic Archipelago tradition. The Islamic Arts and Culture Institute as a non-governmental organization in the Sub-District of Kasimbar annually organizes cultural events in caring for the Nusantara Islamic traditions in the Sub-District of Kasimbar. Qualitative research is used as a method for dissecting data and information obtained from the results of the interviews. The results showed that the tradition that was staged in the cultural event indirectly was an effort to care for the Islamic Archipelago tradition